A PLATONIC VIEW OF THE POLITICAL ORDER - Wellington, Ajith (South Asian Journal of Religion and Philosophy (SAJRP), 2021)
Politics, a noble discipline, can generally be defined as the activities associated with the governance of a country. Sadly, this noble activity has been deprived of its noble character by those engaged in politics. Truth and politics have never been on good and friendly terms with one another and lies have always been a justified and glorified tool in political dealings. The world’s hope for a humanely and socially better order depends on the political order. The progress or the regress of a country is determined by the degree of transparency in political institutions. Unfortunately today, for many involved in politics, truth is not their forte. Virtue is not their ambition. Development of the soul is not their aim. The people who elected them to power are not their concern. Plato was of the opinion that either philosophers become politicians or politicians accept the values of philosophy. Here, by philosophers, he intends those who love virtue; those who love humanity; those whose sole concern is the welfare and well-being of the people.